Rastreability of bovine meat and bone meal using the stable isotope technique in egg production - Denadai, Juliana Célia [UNESP] (2021)
The present study aimed to verify whether the inclusion of other ingredients in the diet of laying hens could interfere with the traceability of bovine meat and bone meal (BMBM) in eggs through stable carbon and nitrogen isotope analysis. Two hundred and fifty-six white laying hens were used and randomly distributed into eight treatments composed of: CONTROL: control diet; GLUTEN: control diet + corn gluten; YEAST: control diet + yeast; GLUTEN + YEAST: control diet + corn gluten + yeast; BMBM: control diet + 4.5 % BMBM; BMBM + GLUTEN: control diet + corn gluten + 4.5 % BMBM; BMBM + YEAST: control diet + yeast + 4.5 % BMBM; BMBM + GLUTEN + YEAST: control diet + corn gluten + yeast + 4.5 % BMBM. The isotopic results were subjected to multivariate analysis of variance (MANOVA) and LDA multivariate linear discriminant analysis. At 28 days, the eggs of the birds given diets without the addition of BMBM differed from the CONTROL group. The yolks showed that all treatments were significantly different from the CONTROL, and at 56 days, all eggs and egg yolks were different from the CONTROL. At 28 days, albumen was significantly different for all CONTROL experimental treatments; however, at 56 days, the YEAST treatment showed no difference from the control. Thus, it was concluded that even with the addition of other ingredients, the isotope technique is still able to detect the BMBM in eggs.